Knowledge, attitude and preventive practices of type 2 diabetes in people of Parbat district. - Shretha, Pratibha (2015)
ABSTRACT: This study was focused on studying the knowledge, attitude and preventive practices related to type 2diabetes. For this, an analytical cross-sectional study was conducted in Kushma Municipality. The general objective of this study was to study knowledge, attitude and preventive practices related to type 2diabetes. The study was carried out thorough semi structured questionnaire. Data were collected by using multistage cluster sampling method. Out of 211 respondents, 40.3% respondents had good knowledge and 59.7% had poor knowledge whereas 80.1% respondents had positive attitude and 19.9% had negative attitude. 8.1% were found as diabetic. 26.5% were from the age group 29-39 years and the average mean age was 43 years. 27.5% were illiterate or had no formal education, 15.2% had studied primary level, 33.2% had studied secondary level and rest 24.2% had higher education. Most of the respondents were Hindus (94.8%). Regarding the occupation of the respondents were business (42.7%) followed by farmer (38.4%), housewife (13.7%) and employer (5.2%). Out of 194 non-diabetic respondents, it is found that only 20.6% ate salads, vegetables and fruits regularly and 8.9% most of the respondents consumed junk food from3-4 days to almost every day. It is also found that most of the respondents (81.4%) consumed sweet occasionally showing good preventive practices of people and only 4.6% of the respondents consumed sweet regularly while in case of saturated fat intake around 14% respondent intake it regularly showing need of intervention to promote healthy fat intake. And about smoking and drinking alcohol almost 90% of the respondents did have no habits of drinking alcohol. Thus, to aware people about diabetes health education advocacy and health promotion programs such as screening and healthy living are the key strategies need to adopted by the health personnel and concerned authorities. Key words :Knowledge, attitude, preventive practices, Diabetes mellitus and Kushma